(untitled) - Nelson, Sandra S. (Chicago, 2001)
Design a planning process customized to your setting with the help of Nelson's do's and dont's, in-depth reports of Anytown Library's experience with the process, and reproducible workforms. allocate resources based on current and future needs.
Keywords: Public libraries,Public libraries,Public libraries,Public libraries,Resource allocation; Planning,Planning,Administration; United States,United States,Administration